2012
DOI: 10.4304/tpls.2.9.1841-1848
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies and Vocabulary Size of Iranian EFL Learners

Abstract: Abstract-The present study aimed to determine the relationship between language learning strategies and vocabulary size in Iranian EFL learners. Therefore, 150 Zoha English Language Learners were given Oxford university and Cambridge university placement test. Oxford strategies inventory for language learning (SILL) were used, as well. According to Brown (2000) taxonomy, three classification of strategies as metacognitive, cognitive, social/affective strategies were included in the present study. Besides, Voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…Second, the results showed that language learning strategies have benefited the Saudi students with higher vocabulary level or have significant usage of all learning strategies. This is partially in line with Alhaysony, (2012), Ansarin et al, (2012), (Alhaisoni, 2012a) as all these studies specify Cognitive and Metacognitive strategies to be the most favourable strategies for Saudi learners. However, the present study shows that students with high vocabulary level (2000 words) focus equally on all language learning strategies while learning new vocabulary.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Second, the results showed that language learning strategies have benefited the Saudi students with higher vocabulary level or have significant usage of all learning strategies. This is partially in line with Alhaysony, (2012), Ansarin et al, (2012), (Alhaisoni, 2012a) as all these studies specify Cognitive and Metacognitive strategies to be the most favourable strategies for Saudi learners. However, the present study shows that students with high vocabulary level (2000 words) focus equally on all language learning strategies while learning new vocabulary.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, students with bigger vocabularies showed frequent use of all strategy types. However, though some studies (Alhaisoni, 2012a,b;Ansarin et al, 2012) indicate that Meta-cognitive and Cognitive strategies were the most used among L2 learners, this study indicates that higher vocabulary size L2 learners use all the strategies equally, and the lower vocabulary size L2 learners use the Meta-cognitive strategy more than other strategies. In a similar study on Chinese EFL learners, Ping and Siraj (2012) found that the students lack use deep cognitive and meta-cognitive strategies as oral repetition or dictionary consultation were the most favoured strategies while semantic encoding was the least commonly used.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The use of multiple strategies depends on the learner's proficiency in the target language. Ansarin, Zohrabi, and Zeynali (2012) found that the learners with higher levels of proficiency used multiple language learning strategies more frequently than the other learners. Abadi and Baradaran (2013) found a positive relationship between the use of learning strategies and learner autonomy in both intermediate and advanced level language learners, but the relationship was stronger in advanced learners.…”
Section: Review Of the Literaturementioning
confidence: 90%
“…Some of these processes allow students to become more self-directed and autonomous learners (Lee, 2010;Oxford, 1990). Furthermore, research has shown that there is a positive relationship between the frequency of using cognitive processes and affective variables and the level of competence in different academic areas (Ansarin, Zohrabi, & Zeynali, 2012;Oxford, 1990;Ting & Chao, 2013). Moreover, cumulative research has found positive impacts of cognitive processes and affective variables on academic achievement (e.g., Strang, 2014;Ting & Chao, 2013).…”
Section: Cognitive Processes and Affective Variables: Definition And mentioning
confidence: 99%